Gesondheidsvoorligting by swanger vroue - M.E. Bester (AOSIS, 1992)
Health education and information in pregnancy must be a priority, despite the lack of instruments to evaluate the effectiveness of the education and the fact that positive results cannot be guaranteed. During research done for a Masters degree on the utilization of antenatal services by high risk primigravidae at the Tygerberg hospital, patients were interviewed on various aspects that are important during pregnancy, like family planning, breastfeeding, smoking and danger signs that may occur during pregnancy.